Numerical analysis of heat transfer and nanofluid flow in a triangular duct with vortex generator: two-phase model - Ahmed, Mirghani Ishag; Ahmed, Hamdi E.; Yusoff, M.Z.; Hawlader, M.N.A. (Wiley-BLACKWELL, 2014)
Laminar forced convection heat transfer and nano-fluids flow in an equilateral triangular channel using a delta-winglet pair of vortex generators is numerically studied. Three nanofluids, namely; Al2O3, CuO, and SiO2 nano-particles suspended in an ethylene glycol base fluid are examined. A two-phase mixture model is considered to simulate the governing equations of mass, momentum and energy for both phases and solved using the finite volume method (FVM). Constant and temperature dependent properties methods are assumed. The single-phase model is considered here for comparison. The nano-particle concentration is assumed to be 1% and 4% and Reynolds number is ranged from 100 to 800. The results show that the heat transfer enhancement by a using vortex generator and nano-fluids is greater than the case of vortex generator and base fluid only, and the latest case provided higher enhancement of heat transfer compared to the case of a base fluid flowing in a plain duct. Considering the nano-fluid as two separated phases is more reasonable than assuming the nano-fluid as a homogeneous single phase. Temperature dependent properties model provided higher heat transfer and lower shear stress than the constant properties model. C⃝2014 Wiley Periodicals, Inc. Heat Trans Asian Res, 0(0): 1–21, 2014; Published online in Wiley Online Library (wileyonlinelibrary.com/journal/htj). DOI 10.1002/htj.21163